Dinamika Pertahanan Australia Tahun 1976-2000Â - , ADIWENA NUGROHO, Rochdi Mohan Nazala, MSA., M.Lit. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Australiaâs defence between 1979-2000 had passed various changes and dynamics within âself Relianceâ framework. The dynamics which were happened within this period is an Australian attempt to adaptation with all situations Australia had to deal with . Therat and situation change emerged within Australia surrounding region had become as a major concern for Australiaâs defence. Defence is one of important aspect for Australia survival, as âwhiteâ and âwestâ country surrounding by Asian and Pacific nation . Before âself relianceâ was introduced in 1979, Australiaâs defence policy in concerned to seeking commitment of friendly power and shaping regional security environment to provide security for Australia Nation. But after they changed defence doctrine to âself relianceâ, Australia should provide their own security, with their own resources. And for 25 years (1979-2000), Australia struggled for self reliance. Keyword: Australia, self-reliance, threat, communism, regional security,